2021
DOI: 10.31744/einstein_journal/2021ao6721
|View full text |Cite
|
Sign up to set email alerts
|

The delay of breast cancer diagnosis during the COVID-19 pandemic in São Paulo, Brazil

Abstract: The delay of breast cancer diagnosis during the COVID-19 pandemic in São Paulo, Brazil O atraso no diagnóstico do câncer de mama durante a pandemia da COVID-19 em São Paulo, Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 12 publications
0
18
0
7
Order By: Relevance
“…An initial 2451 citations were identified for title and abstract screening, of which 77 were eligible for inclusion ( Fig. 1 ) [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial 2451 citations were identified for title and abstract screening, of which 77 were eligible for inclusion ( Fig. 1 ) [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ,…”
Section: Resultsmentioning
confidence: 99%
“…A subtotal of 41 [ 14 , 15 , 20 , 21 , 29 , 30 , [32] , [33] , [34] , 37 , 40 , 42 , 44 , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ] and 12 [ 20 , 21 , 42 , 65 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] ] studies reported diagnosis, and breast imaging outcomes, respectively. Key results from the individual studies are summarised narratively below, and presented in more detail in Table 2 and AppxTable F.6-F.8 ( Appendix F ).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies have confirmed the predicted diagnostic delay [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In a study conducted in Taiwan, Tsai et al [ 9 ] reported that admissions to breast outpatient clinics in hospitals decreased by 37% during the lockdown period, and breast cancer screening decreased by 22%.…”
Section: Discussionmentioning
confidence: 86%
“…In Brazil, data from DATASUS, an open access database of the Brazilian public healthcare system, show a progressive increase in the number of screening mammograms from 2010 to 2018 20 . However, a retrospective cohort study performed in a private hospital in São Paulo, Brazil, showed a decrease of 78.9% in the number of breast exams in the first 90 days of COVID-19 social isolation measures in comparison to the same period in the previous year 21 . Moreover, almost 70% of responders of an electronic survey with members of the Brazilian Society of Mastology declared they have changed their management approach of BC during the pandemic 22 .…”
Section: Discussionmentioning
confidence: 94%